Plant Monitoring Using a Web-View-Based Android Application as a Realization of the Implementation of the Smart Agriculture Concept - Supriyanto Supriyanto; Rohmat Rohmat (Jurnal Rekayasa Elektrika, 2023)
The concept of Smart Farming has been adopted by utilizing microcontrollers, sensor devices, and actuators to regulate plant conditions. However, the communication methods with farmers, such as text messaging applications, are considered ineffective due to their limited features, and farmers cannot control monitoring devices. To address this issue, we developed a web-view-based application named Prospherine Smart Farming using PHP, Java, and MongoDB. The Software Development Life Cycle (SDLC) methodology was employed to ensure the proper functioning of the application. This application has comprehensive features that enable farmers to control monitoring devices, even remotely, and provide continuous information about farming conditions. Testing was conducted to ensure that all features functioned properly, and feedback was obtained from farmers. The research results indicate that using the Prospherine Smart Farming Application positively impacts farming activities. With this application, farmers can monitor their farming conditions in real-time and take necessary actions to enhance crop yields. The Prospherine Smart Farming Application can potentially improve agricultural efficiency and assist farmers in tackling challenges in the digital era.